The Influence of financial literacy on the peformance and sustainability of MSMEs in SIDOARJO - Adi Yudha Pratama; Ahmad Zaki (Institute of Computer Science (IOCS), 2024)
This research aims to investigate the influence of financial literacy on the performance and sustainability of MSME businesses in Sidoarjo. Financial literacy is an individual's ability to understand and manage finances well. This research was conducted because there are still many MSME players who have a low level of financial literacy, which can affect the performance and sustainability of their business. This research uses a quantitative approach with a survey method. The sample used in this research was 50 respondents from U S MKM business actors in Sidoarjo who were selected using a purposive sampling technique. Data was collected through questionnaires and analyzed using multiple linear regression techniques. The research results show that financial literacy has a positive and significant effect on the performance and sustainability of MSME businesses in Sidoarjo. These results show that the higher the level of financial literacy of MSME actors, the better their performance and business sustainability. Apart from that, the research results also show that other factors such as business experience, access to financial resources, and government support also have a positive influence on the performance and sustainability of MSME businesses in Sidoarjo, so that MSME players can gain a better understanding of finance and strengthen performance and sustainability of their business